2014
DOI: 10.1007/s13593-014-0247-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and managing soil biodiversity: a major challenge in agroecology

Abstract: International audienceSoils are living environments in which particularly abundant and diverse microbiome and fauna are evolving. The resulting biological functioning has a direct impact not only on soil fertility but also on a series of ecosystems services. Thus, microbial communities are involved in geochemical cycles in which microbial enzymes catalyse the different steps. Modulation of the corresponding activities is essential as these affect plant growth and environmental quality. In general, biodiversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 75 publications
0
53
0
4
Order By: Relevance
“…trichogram in maize) and other service-providing organisms (e.g. azotobacters, probiotics, arbuscular mycorrhizal fungi), soil biostimulants and bioinoculants, farmers seek to develop ecological processes underpinning ecosystem services which naturally arise in diversified ecosystems (Lemanceau et al 2015;Philippot et al 2013). They can also use biopesticides to avoid eco-toxicity of chemical pesticides.…”
Section: Biological Input-based Farming Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…trichogram in maize) and other service-providing organisms (e.g. azotobacters, probiotics, arbuscular mycorrhizal fungi), soil biostimulants and bioinoculants, farmers seek to develop ecological processes underpinning ecosystem services which naturally arise in diversified ecosystems (Lemanceau et al 2015;Philippot et al 2013). They can also use biopesticides to avoid eco-toxicity of chemical pesticides.…”
Section: Biological Input-based Farming Systemsmentioning
confidence: 99%
“…While their effects are well known, and their efficacy has been demonstrated by research on some iconic living inputs (e.g. inoculation of Rhizobia in leguminous cropping systems; Lemanceau et al 2015), the actual effects of many biological inputs such as biostimulants have not been soundly demonstrated at the field level (Reeve et al 2016). Moreover, they generally have low resilience, leading farmers to apply Fig.…”
Section: Biological Input-based Farming Systems In Globalised Commodimentioning
confidence: 99%
“…The extra radicular hyphae increase the exploitation area of associated plants, which results in an efficient usage of the soil resources, together with the promoted growth and development (Brundrett and Ashwath, 2013;Conversa et al, 2012;Garg and Chandel, 2010;Jayne and Quigley, 2014;Koltai and Kapulnik, 2010;Lambers et al, 2009). Inoculating the soil had beneficial results in the productive ecosystems, especially when the indigenous mycorrhizal flora is not infectious or efficient enough (Hoeksema et al, 2010;Lemanceau et al, 2015;Rillig et al, 2014). The success of mycorrhizal inoculum depends on the capacity to compete for resources of alien species and the association speed with the rhizospheres plants to which these are introduced to (Garg and Pandey, 2015;Gianinazzi et al, 2010;Vicente-Sánchez et al, 2014;Watts-Williams and Cavagnaro, 2014;Wezel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the high number of species in microbial communities compared to communities of macroorganisms would lead to an even higher functional redundancy, so that a reduction of microbial species would not matter for ecosystem functioning (Franklin andMills 2006, Wertz et al 2006). However, just as for macroorganisms, this redundancy is essential for ecosystem stability as species with differing sensitivities to environmental conditions can support ecosystem functions upon environmental changes (Lemanceau et al 2015). In support of this concept, studies repeatedly found a high number of taxa that fluctuate in abundance in space and time, the so called conditionally rare taxa (Shade et al 2014).…”
Section: Functions Of Rare Bacteriamentioning
confidence: 99%
“…As a consequence, it has been suggested to improve the indigenous community in order to enhance its plant-beneficial properties . As a first step towards this goal, Lemanceau et al (2015) proposed to identify both plant genotype and compatible bacterial strains in the soil that together show the best performance. Second, practices could be tested to promote these strains within the community.…”
Section: Functions Of Rare Soil Bacterial Species-beneficial or Harmful?mentioning
confidence: 99%